TUMOR MARKERS IN RATS WITH RENAL TUMOR INDUCED BY N-ETHYL-N-HYDROXYETHYLNITROSAMINE - Okajima, Eigoro; Yamaguchi, Hisako; Kitahori, Yoshiteru; Hiasa, Yoshio; Matsuki, Hisashi; Hirao, Yoshihiko; Uemura, Hirotsugu; Samma, Shoji; Ozono, Seiichiro; Kitagawa, Hisayo; Tabata, Shoichi (Journal of Toxicologic Pathology, 1990)
Renal carcinomas were induced by N-ethyl-N-hydroxyethylnitrosamine (EHEN) followed by trisodium nitrilotriacetate monohydrate (NTA) in Wistar rats. In these rats, various parameters which are clinically used as tumor markers were examined. Renal tumors developed in 6 (37.5%) of 16 rats treated with EHEN alone and in 14 (82.4%) of 17 rats treated with EHEN and subsequently with NTA. When various parameters were compared between these two groups and the control group, RBC, Hb Al-P, LDH, BUN, Cr, and Ca in the former two groups differed significantly from those values of the untreated controls. In the EHEN-treated rats (Group 1 and 2), erythropoietin (EP) was higher in the tumor-bearing group than in the tumor-free group (p<0.025), although no other significant difference was observed. As compared to the untreated controls, tumor-bearing rats showed significant elevation in RBC (p<0.005). Cr (p<0.005), and EP (p<0.05) and significant reduction in Hb (p<0.005). Al-P (p<0.005), and LDH (p<0.05). Therefore, the significant difference in RBC, Hb, Al-P, LDH, and Cr seems to be attributable to the effect of EHEN and NTA. These results suggest that EP is specifically elevated in rats with renal tumor.